Design and analysis of quantitative research in music education - Miksza, Peter ca. 20./21. Jh; Elpus, Kenneth ca. 20./21. Jh (Oxford University Press, 2018)
This work provides a foundational understanding of quantitative inquiry methods suitable for music education research, updating and expanding the tools that music researchers have at their disposal for conceptualizing and analyzing data pertaining to music-related phenomena